The contribution of agent-based simulations to conservation management on a Natura 2000 site. (1st March 2016) - Dupont, Hélène; Gourmelon, Françoise; Rouan, Mathias; Le Viol, Isabelle; Kerbiriou, Christian
Abstract: The conservation of biodiversity today must include the participation and support of local stakeholders. Natura 2000 can be considered as a conservation system that, in its application in most EU countries, relies on the participation of local stakeholders. Our study proposes a scientific method for participatory modelling, with the aim of contributing to the conservation management of habitats and species at a Natura 2000 site (Crozon Peninsula, Bretagne, France) that is representative of in landuse changes in coastal areas. We make use of companion modelling and its associated tools (scenario-planning, GIS, multi-agent modelling and simulations) to consider possible futures through the co-construction of management scenarios and the understanding of their consequences on different indicators of biodiversity status (habitats, avifauna, flora). The maintenance of human activities as they have been carried out since the creation of the Natura 2000s zone allows the biodiversity values to remain stable. Extensive agricultural activities have been shown to be essential to this maintenance, whereas management sustained by the multiplication of conservation actions brings about variable results according to the indicators. None of the scenarios has a positive incidence on the set of indicators. However, an understanding of the modelling system and the results of the simulations allow for the refining of the selection of conservation actions in relation to the species to be preserved. Highlights: A scientific method for participatory modelling at a Natura 2000 site is proposed. A companion modelling was developed to consider possible futures. Stakeholders validated conceptual model and biodiversity indicators. Stakeholders were involved in the co-construction management scenarios. Extensive agricultural activities is essential for maintain and enhance biodiversity.